Kesalehan Sosial dalam mewujudkan Ketenangan lahir dan Bathin Perspektif Filsafat Islam - Irsal Irsal (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This study examines social piety in realizing inner and outer peace from the perspective of Islamic philosophy. The research aims to analyze the concept of social piety, its relationship with human well-being, and its relevance in addressing the spiritual and social crises of modern society. This study employs a qualitative method with a library research approach by analyzing various sources related to Islamic philosophy, social ethics, spirituality, and psychological well-being. The findings reveal that social piety in Islamic philosophy is not limited to individual religious devotion but also includes social responsibility, empathy, justice, solidarity, and concern for humanity. Thinkers such as Al-Ghazali, Ibn Miskawayh, and Al-Farabi emphasize that true happiness and peace can only be achieved through the balance between spiritual values and harmonious social relations. Furthermore, the study finds that modern crises such as individualism, materialism, alienation, and mental health problems are closely related to the decline of social and spiritual values in society. Therefore, social piety serves as a philosophical and ethical solution in creating psychological well-being, social harmony, and holistic human happiness. This study concludes that social piety in Islamic philosophy is highly relevant as a humanistic paradigm for achieving both inner and outer peace in contemporary society.